The Gaia Parallax Discrepancy for the Cluster Pismis 19 and Separating δ Scutis from Cepheids - Daniel Majaess; Charles J. Bonatto; David G. Turner; Roberto K. Saito; Dante Minniti; Christian Moni Bidin; Danilo González-Díaz; Javier Alonso-Garcia; Giuseppe Bono; Vittorio F. Braga; Maria G. Navarro; Giovanni Carraro; et al. (The Astrophysical Journal)
Pre-Gaia distances for the open cluster Pismis 19 disagree with Gaia parallaxes. A Two Micron All Sky Survey (2MASS) JK _s red clump distance was therefore established for Pismis 19 (2.90 ± 0.15 kpc), which reaffirms that zero-point corrections for Gaia are required. OGLE GD-CEP-1864 is confirmed as a member of Pismis 19 on the basis of DR3 proper motions and its 2MASS+Vista Variables in the Vía Láctea color–magnitude position near the tip of the turnoff. That 0.3 day variable star is likely a δ Scuti rather than a classical Cepheid. The case revealed a pertinent criterion to segregate those two populations in tandem with the break in the Wesenheit Leavitt Law (≃0.5 day). Just shortward of that period discontinuity are δ Scutis, whereas beyond the break lie first overtone classical Cepheids mostly observed beyond the first crossing of the instability strip.